Pengaruh Sosial Media terhadap Mental Health Gen-Z - Sitanggang, Andri Sahata; Azkia, Hafidz Fathi; Sutrisno, Endar; FH, Zahra; Eka, Dela (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The use of digital platforms today can influence various aspects of life, such as acting as a means of entertainment or communication. However, if digital platforms are not used properly, this will trigger mental health problems. Users of social media themselves have reached the entire community, especially generation Z. Generation Z as one of the active users, generally can experience problems that can create social comparisons, increase depression and anxiety, as well as unrealistic expectations. The purpose of writing is to analyze the influence of social media on mental health in generation Z. The type of research used in this research is based on qualitative research. The results obtained are that generation Z's mental health is influenced by the use of social media. Excessive use of social media certainly has a negative impact on the mental health of generation Z. This is proven through observations that generation Z generally has mental health problems, such as feeling lonely, anxious, stressed and depressed. Mental health is connected to physical health. Individuals must use social media wisely, because if generation Z is not wise in using social media there will certainly be risks in the future.